2002
DOI: 10.1021/jf010864j
|View full text |Cite
|
Sign up to set email alerts
|

Partitioning of Olive Oil Antioxidants between Oil and Water Phases

Abstract: The partition coefficient (K(p)) of the natural phenolic antioxidant compounds in the olive fruit between aqueous and olive oil phases was determined. The antioxidants of olive oil are either present in the olive fruit or formed during the olive oil extraction process. The antioxidants impart stability to and determine properties of the oil and are valuable from the nutritional point of view. The olive oil antioxidants are amphiphilic in nature and are more soluble in the water than in the oil phase. Consequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
205
1
5

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 303 publications
(222 citation statements)
references
References 17 publications
11
205
1
5
Order By: Relevance
“…Olive oil contains 2% of the total phenolic content of whole olive fruits, while the remaining 98% is present in olive mill waste (Rodis et al 2002). Olive fruits are considered as a rich source of phenolic compounds with a wide array of biological activities (Obied et al 2005).…”
Section: Universidad Del Bío -Bíomentioning
confidence: 99%
See 1 more Smart Citation
“…Olive oil contains 2% of the total phenolic content of whole olive fruits, while the remaining 98% is present in olive mill waste (Rodis et al 2002). Olive fruits are considered as a rich source of phenolic compounds with a wide array of biological activities (Obied et al 2005).…”
Section: Universidad Del Bío -Bíomentioning
confidence: 99%
“…To date, three aspects of antioxidant activity have been evaluated in olive cakes; antioxidant potency (Ranalli et al 2003, Shahidi andNaczk 2004), anti-radical activities and radical scavenging activities (Lesage-Meessen et al 2001, Shahidi andNaczk 2004). However, little information has been reported on the recovery of phenolic compounds from olive cake as a potential source of bioactive compounds for the pharmaceutical and nutraceutical industries (Rodis et al 2002).…”
Section: Universidad Del Bío -Bíomentioning
confidence: 99%
“…while, although not toxic, the high and repetitive concentration on the surface (disposal sites) can cause serious environmental problems. Studies have shown changes in the physicochemical parameters of soils both within the landfills and the surrounding area [3,4,28]. The long-term olive oil mills waste deposition can lead to future serious degradation of soil and groundwater quality.…”
Section: Discussionmentioning
confidence: 99%
“…potassium and phosphorus), as well as grease. They are also characterized by low resistivity (0.7-5 Ohm-m), acid PH (4.0-5.5), increased Biochemically Oxygen Demand (40-95 g/l) and Chemically Oxygen Demand (50-180 g/l) values and their toxicity is mainly dependent on their high concentration of phenolic compounds [4].…”
Section: Introductionmentioning
confidence: 99%
“…Olive polyphenols, especially oleuropein and hydroxytyrosol, have been studied with respect to their potential preventive effects, including anticarcinogenic, antiatherogenic, and antimicrobial properties (Ryan et al, 2002 and the temperature (Artajo et al, 2007). According to Rodis et al (2002), the partition coefficient (K p ) is the ratio of concentrations in the oil and water phases at equilibrium. This coefficient was estimated to be as low as 0.0006 for oleuropein to a maximum of Nonetheless, a detailed material balance was not described for the three-phase extraction method.…”
Section: Introductionmentioning
confidence: 99%